2015
DOI: 10.1111/pedi.12263
|View full text |Cite
|
Sign up to set email alerts
|

Insulin degludec in combination with bolus insulin aspart is safe and effective in children and adolescents with type 1 diabetes

Abstract: Insulin degludec (IDeg) once-daily was compared with insulin detemir (IDet) once- or twice-daily, with prandial insulin aspart in a treat-to-target, randomized controlled trial in children 1–17 yr with type 1 diabetes, for 26 wk (n = 350), followed by a 26-wk extension (n = 280). Participants were randomized to receive either IDeg once daily at the same time each day or IDet given once or twice daily according to local labeling. Aspart was titrated according to a sliding scale or in accordance with an insulin:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
1
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 34 publications
9
87
1
14
Order By: Relevance
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the majority of the studies have reported comparable glucose-lowering effects of IDeg and IGlar in patients with type 1 diabetes, as demonstrated by equivalent FPG and HbA1c levels [9,13,[17][18][19]. As mentioned in the introduction, in a 26-week study of pediatric patients with type 1 diabetes of all ages, Thalange et al [13] reported the non-inferiority of IDeg as compared with IDet in regard with changes in HbA1c levels from the baseline. On the other hand, we previously demonstrated an improvement in glycemic control in young adults with type 1 diabetes after changing from IGlar to IDeg [14].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Biester et al [16] reported only that the ultra-long pharmacokinetic properties of IDeg observed in adults were retained in children and adolescents with type 1 diabetes. Recently, Thalange et al [17] reported that IDeg offered glycemic control and frequencies of hypoglycemia similar to those achieved with La of insulin detemir (IDet), but reduced hyperglycemia with ketosis at a once-daily daily injection when used in these age groups of patients with type 1 diabetes.…”
Section: Methodsmentioning
confidence: 87%